Sedative-Hypnotic Effects of Different Extracts and Fractions of Capparis Spinosa L. in Mice - khoramjouy, mona; manaee, maede; sahranavard, shamim; Faizi, Mehrdad (International Pharmacy Acta, 2021)
Introduction: Capparis spinosa L. (Caper) is an aromatic plant growing in dry regions around the Mediterranean area. C. spinosa is shown to have several compounds such as tannins, sterols, alkaloids, polyphenols and flavonoids. Previous studies showed that flavonoids have sedative and hypnotic effects. The aim of this study was evaluating the sedative-hypnotic effects of various extracts and fractions of C. spinosa in different doses. Methods and Results: Maceration method was used for extraction of the aerial part of the plant. All experiments conducted on male NMRI mice (18-25g weight). For evaluation the hypnotic and sedative effects of plant, open field and pentobarbital induced sleep test were used. In this study, animals were treated with different doses of aqueous extract, methanolic extract, methanolic fraction and dichloromethane fraction (i.p.). In pentobarbital induced sleep test, the duration of lack of righting reflex was reported. In open field test, the locomotor activities of mice were calculated by measuring total distance moved in the open field arena. According to the results, the dichloromethane fraction decreased the total distance moved in the open field test (ED50 = 66.6 mg/kg) and also increased the sleep duration in pentobarbital induced sleep test (ED50 =18.7 mg/kg) compared with other extract and fractions groups. Conclusion: In conclusion, the dichloromethane fraction of C. spinosa has hypnotic and sedative effects compared to the other extract and fraction groups. Further studies are necessary to find the active components responsible for the several effects of the dichloromethane fraction and the exact mechanism of action of these effects.